2011
DOI: 10.1063/1.3624456
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-portable explosives sensor based on a CMOS fluorescence lifetime analysis micro-system

Abstract: This work explores the use of a green-light-emitting copolymer as a chemosensor to detect nitroaromatic-based explosive vapors by recording photoluminescence (PL) and time-resolved PL decay. We show successful detection of 10 ppb 1,4-dinitrobenzene (DNB) vapor. Both a conventional time-correlated single photon counting (TCSPC) device and CMOS time-resolved fluorescence lifetime micro-system are used in the DNB detection. An ultra-portable on-site explosive sensor based on the micro-system has also been demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The detection system was attached on one side of the sensing chamber used in previous explosives detection studies [6][7][8]12]. Clean nitrogen was purged for a few seconds through the chamber prior to the 2,4-DNT vapour-line being introduced.…”
Section: System Response To 24-dnt Vapour Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection system was attached on one side of the sensing chamber used in previous explosives detection studies [6][7][8]12]. Clean nitrogen was purged for a few seconds through the chamber prior to the 2,4-DNT vapour-line being introduced.…”
Section: System Response To 24-dnt Vapour Flowmentioning
confidence: 99%
“…There have been extensive studies on conjugated polymer films for explosives detection [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The PL lifetime is less affected by environmental factors, such as stray light, which should make the sensor more reliable. We have recently reported an ultra-portable compact silicon-based TCSPC micro-system, which could be used for real-time in-field explosive detection [18]. The DFB polymer laser were found to have an even greater responsivity compared to steady-state PL quenching, which is leads to the potential for ultra-lowconcentration explosives sensing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the CDTG copolymer has a relatively high solid-state photoluminescence quantum yield (PLQY) of 61% [18]. Prior to making a laser, the potential of the copolymer as a gain material was investigated by ASE measurement.…”
Section: Gain Properties and Dfb Laser Sensingmentioning
confidence: 99%
“…The explosive nitro-aromatic analyte DNB (purchased from Sigma-Aldrich and used as received) was used during this investigation as it is chemically similar to the explosive TNT and highly electrondeficient [22]. Explosive solutions were prepared by dissolving a certain amount of DNB in 4ml of acetone and the sample concentration range from 1mg/ml, 2mg/ml, 3mg/ml, 4mg/ml, 5mg/ml (which is 6mM, 12mM, 18mM, 24mM, 30mM), the sample was stirred at room temperature for one hour in order to dissolved completely and stored in amber vials at 2-8 o C to prevent degradation.…”
Section: Preparation Of the Explosives Samplementioning
confidence: 99%